Anti-Mycobacterial Activity Of Some Synthesized 2 (21-Phenyl-4-Benzidinyl-5-Oxo-Imidazoline-1yl-Amino-6 Fluoro-7-Substituted (1, 3) Benzothiazoles - B.S. SATHE,; E. JAYCHANDRAN,; V. A. JAGTAP,; G.M SREENIVASA, (International Journal of Pharma and Bio Sciences, 2010)
2[2’- Phenylidinyl- 5’- oxo- imidazoline- 1yl- amino] -6 fluoro- 7- substituted (1,3) benzothiazoles have been synthesized and screened for antitubercular activity. Literature revealed that vast majority of benzothiazoles and imidazole compounds are known to possess pharmacologically proven therapeutic potentials. Though extensive research work is reported on benzothiazoles, reactively very little is known so for about fluorobenzothiazole incorporated imidazolines with fluorine at 6th position. The reaction of 6- fluro-7-chloroaniline1 with potassium thiocynate (KSCN) in presence of bromine and glacial acetic acid and ammonia to get 2-amino 6- fluro-7-chloro(1,3) benzothiazoles2-5 (1) which was further treated with hydrazine hydrate in presence of ethylene glycol and sulphuric acid to yield 2-hydrazino-6-fluoro-7-chloro(1,3) benzothiazoles(2). It was reacted with prepared Oxazolone i.e.2phenyl-4-benzylidine-5-oxazolone (3) to yield 2[2’- Phenylidinyl- 5’- oxo- imidazoline- 1yl- amino] -6 fluoro- 7- chloro(1,3) benzothiazole(4), which was treated with variety of aromatic anilines in presence of DMF to yield different derivatives (5a-5i).